ANALISIS INCOME OVER FEED COST DAN STATUS NUTRISI KAMBING PERANAKAN ETTAWA PADA MASA LAKTASI YANG DIBERI PAKAN SECARA TRADISIONAL DI DESA PURWOBINANGUN, PAKEM, KABUPATEN SLEMAN - , EDY SANTOSO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The study was conducted to analyze income over feed cost and nutrition status of peranakan ettawa goat during lactation period fed traditionally. The study was conducted in Purwobinangun village, used 15 ewes owned by four farmers. The study was carried out for 9 months, the first months for fed sampling and interview with farmers, the next month for analysis feed dry matter, organic matter and protein matter consumed by ewe goat. The study obtained the average body weight gain 1,96±0,29 kg, average milk production 11,99±6,17 liter, average nutient consumed of dry matter 1.067±169 g/ewe, average nutrient consumed of organic matter 970±154 g/ewe and average nutrient consumed of protein matter 169±41 g/ewe. Income over feed cost was Rp. 150.974,25/ewe, and income total Rp. Rp. 147.036,75 after reduced total cost, and protein needed 118 g/ewe but the farmers give 169 g/ewe. It can be concluded that the traditional fed available at sites generate positive Income Over Feed Cost and the farmers still get profit, and than was fullfiled nutrient needed of Peranakan Ettawa goat lactation period. Key words: Peranakan Ettawa goat, Fed traditionally, Nutrient consumed, Income Over Feed Cost